HOXC13-AS Induced Extracellular Matrix Loss via Targeting miR-497-5p/ADAMTS5 in Intervertebral Disc - Jing, Wanli; Liu, Wei (Frontiers in Molecular Biosciences, 2021)
Background/Aims: LncRNAs are a new modulator in the development of intervertebral disc degeneration. However, the functional role and mechanism of HOXC13-AS in intervertebral disc degeneration remain unclear. Methods: qRT-PCR analysis was performed to measure the relative expression levels of HOXC13-AS and miR-497-5p, and the levels of IL-1β, IL-6 and TNF-α in the medium supernatant were analyzed by ELISA. The related mechanism between HOXC13-AS and miR-497-5p was detected by luciferase assays. Results: The results revealed that TNF-α and IL-1β induced HOXC13-AS expression in NP cells. HOXC13-AS was overexpressed in IDD specimens compared to control specimens, and higher expression of HOXC13-AS was correlated with high Pfirrmann scores. Ectopic expression of HOXC13-AS promoted MMP-3 and ADAMTS4 and inhibited aggrecan and collagen II expression in NP cells. Furthermore, overexpression of HOXC13-AS increased the expression of inflammatory cytokines, including IL-1β, IL-6 and TNF-α. Our results demonstrated that TNF-α and IL-1β induced ADAMTS5 expression and suppressed miR-497-5p expression. miR-497-5p was downregulated in IDD specimens compared to control specimens, and the lower expression of miR-497-5p was correlated with high Pfirrmann scores. The miR-497-5p level was negatively proportional to HOXC13-AS expression in IDD specimens. Luciferase analysis data indicated that ADAMTS5 was a direct target gene of miR-497-5p. HOXC13-AS induced inflammatory cytokine expression and ECM degradation by modulating miR-497-5p/ADAMTS5. Conclusion: HOXC13-AS may be a treatment target for IDD.